CLINICAL FEATURES OF VISUAL ACUITY,CONTRAST SENSITIVITY, AND COLOR VISIONOF OPTIC NEURITIS PATIENTS TREATED WITH STEROIDAT PROF. DR. I. G. N. G. NGOERAH GENERAL HOSPITAL IN 2021-2022 - Sari, Intan Cendana; Putrawati T, A. A. Mas; Wijayati, Made Paramita; Manuaba, I. B. Putra (E-Jurnal Medika Udayana; Vol 14 No 01 (2025): E-Jurnal Medika Udayana, 2025)
Introduction: Optic neuritis (ON) is an inflammation of the optic nerve that can occur alone or in association with neurological inflammatory or infectious disorders, or local or systemic inflammatory diseases. Vision function will return to near normal in weeks or months regardless of treatment, but it will be hastened with corticosteroid treatment. Objective: To determine the clinical features of ON patients and difference of visual acuity, contrast sensitivity and color vision before and after steroid therapy. Methods: Analytical descriptive research with retrospective data collection based on medical records of patients visiting Prof. dr. I. G. N. G. Ngoerah General Hospital in 2021-2022. Statistical analysis regarding comparation of variables before and after treatment used Wilcoxon test. Results: There were 14 patients with equal percentage of males and females, 15-40 years old (64.3%), bilateral cases (57.1%), and atypical neuritis (92.9%). The chief complaint was blurred vision (57.1%) and onset was less than one week (57.1%). Baseline visual acuity log MAR 2,00±0,51, contrast sensitivity and color vision were mostly not evaluable, respectively 57.1% and 85.7%. After steroid therapy, visual acuity reached log MAR 0,93±1,05, contrast sensitivity and color vision reached normal, both 35.7%. Conclusion: The NO patients had an equal percentage of males and females, aged 15-40 years, with bilateral atypical neuritis type. There were differences in visual acuity, contrast sensitivity, and color vision before and after steroid therapy. Whereas clinical features were better after steroid therapy. Keyword: optic neuritis, visual acuity, steroid